Analisis Pengaruh Experiential Marketing terhadap Loyalitas Pelanggan Hotel âXâ Semarang - Putri, Yuwandha Anggia; Astuti, Sri Rahayu Tri (Jurnal Ilmu Ekonomi ASET, 2010)
The objective of this research was to find out: a. how big the influence of sense,feel, think, and relate partially toward customer loyalty of hotel âXâ Semarang; b. how big theinfluence of sense, feel, think, act, and relate simultaneously toward customer loyalty of hotelâXâ Semarang. The samples of this research were 100 customers that were staying or hadstayed in the hotel âXâ Semarang. The sampling technique was accidental sampling. Theanalysis technique was quantitative, with multiple linear regression, t test, and F test. Theresult by using program of SPSS indicated that sense, feel, think, act, and relate had positiveinfluence to customer loyalty. The result of partial hypothesis showed that sense, feel, think,act, and relate had positive significant influence with significance level less than 0.05. So, itcan be concluded the formula hypothesis was correctly proven. The result of simultaneoushypothesis showed that variable of sense, feel, think, act, and relate had positive significantinfluence with significance level F less than 0.05, so Ho was refused and Ha was accepted. Itmeans that the hypothesis which stated âthere was positive and significant influence of sense,feel, think, act, and relate to customer loyalty (Y)â was truly proven.Keywords: sense, feel, think, act, relate, dan loyality.